Remittances and Economic Growth in Transition Countries - KARADAĞ, Metin; ÖNDER, Asiye Özlem; KARYMSHAKOV, Kamalbek (International Journal of Contemporary Economics and Administrative Sciences, 2019)
Migrants’ remittances have become an important development tool because they can raise income and reduce poverty rates in developing countries. These remittances might also promote development by providing funds that recipients can spend on education or health care or invest in entrepreneurial activities. Thus, workers’ remittances are a steadily growing external source of capital for developing countries. In spite of the fact that importance of remittances in total international capital ﬂows are increasing, the relationship between remittances and growth has not been adequately studied. The main aim of this paper is to investigate the impact of remittances on economic growth in the transition countries. For the aim of the study, we test the hypothesis suggested by the Giuliano and Ruiz-Arranz (2005), which states that remittances can substitute for a lack of financial development and hence promote economic growth. Their empirical analysis shows that remittances can promote economic growth in less financially developed countries. We use panel data for the time period between 2001-2012 for the aim of the study. The results of the study suggest that there is a negative significant effect of remittances on economic growth in the transition economies.